2023
DOI: 10.1021/acsami.3c04903
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Doping Mechanism and Interface Strengthening in the Na3SbS4 Electrolyte via Solid-State Synthesis

Abstract: Good-performing sodium solid electrolytes (SSEs) are essential for constructing all-solid-state sodium-ion batteries operating at ambient temperature. Sulfide solid electrolyte, Na 3 SbS 4 (NBS), an excellent SSE with good chemical stability in humid air, can be synthesized with low-cost processing. However, Na 3 SbS 4 -based electrolytes with liquid-phase synthesis exhibit conductivities below milli-Siemens per centimeter. Thus, a series of halogen-doped samples formulated as Na 3−x SbS 4−x M x (0 ≤ x ≤ 0.3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Recently, an even higher conductivity of 10.37 mS cm –1 with a W-doped Na 3 SbS 4 solid electrolyte was achieved by melt-quenching. However, the capacity of the resulting all-solid-state battery deteriorated owing to the instability at the Na/solid electrolyte interface. The high-valence W is easily reduced by metallic sodium, , forming a solid electrolyte interface layer that increases the interface impedance and thus leading to a rapid battery failure. , One of the commonly used strategies to improve the stability of the interface is to optimize the composition of the solid electrolyte by doping. , For instance, the W and O-codoped Na 3 SbS 4 can form passivation decomposition products of Na 2 O at the Na/solid electrolyte interface, thus improving the interfacial stability. It is reported that the introduction of boron in solid electrolytes can form stable compounds, which can inhibit undesirable chemical reactions at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an even higher conductivity of 10.37 mS cm –1 with a W-doped Na 3 SbS 4 solid electrolyte was achieved by melt-quenching. However, the capacity of the resulting all-solid-state battery deteriorated owing to the instability at the Na/solid electrolyte interface. The high-valence W is easily reduced by metallic sodium, , forming a solid electrolyte interface layer that increases the interface impedance and thus leading to a rapid battery failure. , One of the commonly used strategies to improve the stability of the interface is to optimize the composition of the solid electrolyte by doping. , For instance, the W and O-codoped Na 3 SbS 4 can form passivation decomposition products of Na 2 O at the Na/solid electrolyte interface, thus improving the interfacial stability. It is reported that the introduction of boron in solid electrolytes can form stable compounds, which can inhibit undesirable chemical reactions at the interface.…”
Section: Introductionmentioning
confidence: 99%